EURASIP Journal on Wireless Communications and Networking - Jorswieck, Eduard
The overall aim of the EURASIP Journal on Wireless Communications and Networking (EURASIP JWCN) is to bring together science and applications of wireless communications and networking technologies with emphasis on signal processing techniques and tools. It is directed at both practicing engineers and academic researchers. EURASIP Journal on Wireless Communications and Networking will highlight the continued growth and new challenges in wireless technology, for both application development and basic research. Articles should emphasize original results relating to the theory and/or applications of wireless communications and networking. Review articles, especially those emphasizing multidisciplinary views of communications and networking, are also welcome. EURASIP Journal on Wireless Communications and Networking employs a paperless, electronic submission and evaluation system to promote a rapid turnaround in the peer-review process. The journal is an Open Access journal since 2004.